Bioenergy production from residual sludge in microbial fuel cells (Research, Society and Development, 2025)
Inadequate sludge management in oxidation ponds leads to the accumulation of organic matter and pollutants, posing an environmental challenge. Microbial fuel cells (MFCs) offer an innovative solution for bioenergy production and wastewater treatment. This systematic review aims to evaluate the effect of bioenergy production from residual sludge using MFCs through a descriptive analysis of existing scientific literature. The results indicate that single-chamber MFCs achieve up to 2400 mW/m², surpassing double- and triple-chamber systems due to lower internal resistance. Alkaline pretreatment and sludge fermentation increase voltage up to 0.89 V with modified graphite electrodes. A C/N ratio and electrical conductivity above 1700 µS/cm enhance stability and energy efficiency, especially in sludge rich in organic matter. These findings demonstrate that MFCs are a sustainable alternative for residual sludge management, reducing environmental impact and optimizing energy efficiency in wastewater treatment.